ASUHAN KEPERAWATAN PADA TN. S DENGAN CHRONIC KIDNEY DISEASE DI RSUD BANGKINANG - zianfadilla fadilla; Indrawati; Putri Eka Sudiarti; Nia Aprilla (Jurnal Spektrum Kesehatan Indonesia, 2025)
CKD is a global health problem that continues to worsen. Data shows that CKD is the leading cause of death in the world. based on data from the last 1 month obtained from RSUD Bangkinang, there were 27 patients with CKD who were treated in the warrior room. one of the patients in the warrior room with a case of CKD was found "the patient's complaint said that his appetite decreased, the patient said that there was shortness of breath and the body felt tired easily. This condition is an important concern considering its impact on the patient's quality of life and the need for intensive and continuous medical care. This study aims to provide nursing care for patients with CKD at Bangkinang Hospital in 2025. The design used was a case study of a 61-year-old patient with a medical diagnosis of CKD. Nursing care is carried out for 4 days, starting from assessment, diagnosis, planning, implementation, to evaluation. Nursing diagnoses include peripheral perfusion, nutritional deficits, and acute pain. Interventions were carried out based on the Indonesian Nursing Intervention Standards (SIKI), including observation, education, therapy, and collaboration. The results showed improvement in the patient's condition, in the form of reduced grimacing, pain was mild, restlessness was reduced, pain was reduced. In conclusion, the client was able to cooperate during the implementation of each nursing action provided.